2010
DOI: 10.1126/science.1188280
|View full text |Cite
|
Sign up to set email alerts
|

Sfrp5 Is an Anti-Inflammatory Adipokine That Modulates Metabolic Dysfunction in Obesity

Abstract: Adipose tissue secretes proteins referred to as adipokines, many of which promote inflammation and disrupt glucose homeostasis. Here we show that secreted frizzled-related protein 5 (Sfrp5), a protein previously linked to the Wnt signaling pathway, is an anti-inflammatory adipokine whose expression is perturbed in models of obesity and type 2 diabetes. Sfrp5-deficient mice fed a high-calorie diet developed severe glucose intolerance and hepatic steatosis, and their adipose tissue showed an accumulation of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
509
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(550 citation statements)
references
References 25 publications
33
509
6
2
Order By: Relevance
“…In obese rats, Ouchi et al (2010) observed reduced SFRP5 expression and increased Wnt-5a expression. This confirms that detectable serum levels of and SFRP5 are present in obese individuals and these bioactive peptides can be affected by level of nutrition.…”
Section: Pro-inflammatory Adipokines Function Leptinmentioning
confidence: 92%
See 1 more Smart Citation
“…In obese rats, Ouchi et al (2010) observed reduced SFRP5 expression and increased Wnt-5a expression. This confirms that detectable serum levels of and SFRP5 are present in obese individuals and these bioactive peptides can be affected by level of nutrition.…”
Section: Pro-inflammatory Adipokines Function Leptinmentioning
confidence: 92%
“…Yet, obesity leads to decreased SFRP5 expression and increased Wnt-5a expression in adipocytes, activating the c-jun amino (N)-terminal kinase 1 (JNK-1) pathway and triggering a pro-inflammatory response. The activation of JNK-1 impairs the activity of a target protein called insulin receptor substrate-1 (IRS-1) leading to suppressed insulin signaling and development of insulin resistance (Oh, Olefsky, 2010;Ouchi et al, 2010).…”
Section: Pro-inflammatory Adipokines Function Leptinmentioning
confidence: 99%
“…There is strong experimental evidence for the contribution of endogenous Wnt proteins to inflammatory cytokine responses and host defense against pathogens in in vivo models [5,11,20] as well as in a variety of cell culture systems [2,6,13,14,36]. In a model of dietinduced metabolic dysfunction, sFRP5 exerted anti-inflammatory functions in vivo, possibly by interfering with Wnt5a-induced proinflammatory cytokine production [11]. Inhibition of the acyltransferase Porcupine, which is central to posttranslational modification required for functional Wnt proteins [37], improved clearance of nonpathogenic Escherichia coli in vivo [5].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical associations of elevated Wnt expression and pathway activity with infections [2,3,6] and chronic inflammatory diseases [8,9,11] have sparked significant interest in elucidating immune-related functions of Wnt signaling. There is strong experimental evidence for the contribution of endogenous Wnt proteins to inflammatory cytokine responses and host defense against pathogens in in vivo models [5,11,20] as well as in a variety of cell culture systems [2,6,13,14,36]. In a model of dietinduced metabolic dysfunction, sFRP5 exerted anti-inflammatory functions in vivo, possibly by interfering with Wnt5a-induced proinflammatory cytokine production [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation